Airfield and Highway Pavements 2019. selected papers from the International Airfield and Highway Pavements Conference 2019, July 21-24, 2019, Chicago, Illinois - Al-Qadi, Imad L.; Ozer, Hasan; Loizos, Andreas; Murrell, Scott (American Society of Civil Engineers, 2019)
Contains 57 peer-reviewed papers on the testing and characterization of airfield and highway pavements. Topics include: laboratory and field characterization of asphalt binders, modifiers, and rejuvenators; asphalt mixtures and modification; recycled and waste materials in asphalt mixtures; unbound base and subgrade materials; layer stabilization; and recent advances in cementitious materials characterization and concrete pavement technology. This proceedings will be of interest to transportation infrastructure researchers, consultants, designers, project/construction managers, and contractors from around the world.